Climate change impacts on renewable electricity generation. Issue 3 (August 2015) - Cradden, Lucy; Burnett, Dougal; Agarwal, Atul; Harrison, Gareth
Abstract : The generation of renewable energy is strongly related to climate and could be vulnerable as the climate changes in the coming decades. The assessment of the potential risks is a new and evolving area of science. In light of the rapid pace of development and more prominent contribution of renewables to UK electricity generation, this work presents a summary of the current state of knowledge in the field and highlights some of the critical parameters and areas of uncertainty. An assessment of potential changes in the levelised cost of energy is presented, with the caveat that this is entirely based on existing data, which in some cases are highly uncertain. The areas of critical research for both understanding climate and engineering for adaptation are discussed.